Dimensions of Self-Concept in Adolescents: An In-depth Analysis Among Junior High School Students - Dendy Setyadi (Pattimura University, 2024)
This research explores the intricate nature of self-concept, a pivotal element in human behavior and identity formation, encompassing beliefs, thoughts, and perceptions shaping individuals' understanding of themselves and their environment across physical, psychological, and social dimensions, influencing behavior and self-esteem. Focusing on junior high school students aged 13-18 in Bangka Belitung, the study employs a quantitative descriptive approach with 126 participants, employing Rahmat's theory (2013) to gauge self-concept facets. Outcomes reveal that 34% of students perceive their self-concept as moderate, while 4% hold positive views and 32% exhibit above-average self-concepts. Notably, gender-based disparities accentuate the need for tailored interventions. Identification of areas needing improvement via validity testing led to proposed classical guidance topics aimed at augmenting self-concept, including body care, confidence-building, and social interaction. Implications stress the significance of customized interventions, gender-aware strategies, and nurturing positive self-concept for comprehensive student growth, in alignment with educational experts' viewpoints, advocating self-awareness, constructive perspectives, and individualized assistance. These insights advocate holistic approaches to empower students on their path to self-acceptance, personal development, and holistic growth, echoing broader educational objectives and policies, reaffirming the pivotal role of classical guidance in molding students' self-concept.